PENINGKATAN KOMPETENSI GURU PAI DALAM MEMBUAT RPP MELALUI SUPERVISI AKADEMIK BERKELANJUTAN PADA SEKOLAH BINAAN DI KOTA LUBUKLINGGAU - Roaidah; Muhamad Akip; Sujarwo; Candres Abadi (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
This research aims to increase the competency of PAI teachers in making lesson plans through continuous academic supervision at assisted schools in Lubuklinggau City. This type of research is school action research that focuses on the role of academic supervision in preparing lesson plans which consist of two cycles consisting of planning, implementing, observing and reflecting. Techniques and Methods Data collection was carried out by interviews, questionnaires, observation. Research results. In Cycle I, teachers who had made and collected lesson plans from the beginning were continued in Cycle I, meeting 1 and meeting 2. It was found that there was an increase from 37% to 56%, in cycle I, meeting 2, it increased again to 85%, but there was still a discrepancy between teaching and planning. It turns out that the quantity of teachers after continuous supervision has increased. In Cycle II, it can be said that the competence of teachers in compiling lesson plans increased, due to an increase in teachers from 30% to 60% at the end of cycle I, and increased again in Cycle II to 80% of teachers who received a B (Good) grade based on the authenticity of the lesson plan prepared by the teacher. due to scenario compatibility.